An interesting case of melioidosis: a mimicry of pulmonary tuberculosis - Sivasamy, Manoj; R., Shreenidhi; M. K., Nishaanth; M., Jagadeesan; S., Prasanna Karthik (International Journal of Advances in Medicine, 2022)
Melioidosis is caused by Burkholderia pseudomallei which is a soil-dwelling aerobic bacterium reported mostly in tropical and subtropical areas, especially in Asia (Southeast) and Australia (Northern part). Melioidosis is a severe infection that can manifest as chronic debilitating pneumonia mimics pulmonary tuberculosis. Here, we reported a case of melioidosis, in 51-year-old men with poorly controlled type 2 diabetes mellitus. The patient recovered with appropriate intravenous antibiotics and supportive medications.